German Respiratory Society guidelines for diagnosis and treatment of adults suffering from acute, subacute and chronic cough. (August 2020) - Kardos, P.; Dinh, Q.T.; Fuchs, K.-H.; Gillissen, A.; Klimek, L.; Koehler, M.; Sitter, H.; Worth, H.
Abstract: The present 2019 S2k consensus guideline of the German Respiratory Society was written for pneumologists – in contrast to the more general predecessor's S3 guidelines from 2004 to 2010 –, since 2014 the German College of General Practitioners and Family Physicians (DEGAM) published their own cough guidelines. The guidelines contain 48 recommendations agreed upon the consensus and 16 statements, which are explained in the background text in the following nine chapters: epidemiology, physiology, classification, acute, subacute or chronic cough, diagnostics and therapy; an extra chapter was dedicated to chronic idiopathic/refractory cough. Further emphasis of the guidelines is the physiology of cough in anticipation of the introduction of new drugs, as well as detailed treatment for cough triggered by affectations of the upper respiratory tract or gastroesophageal reflux. The guideline should provide the pneumologist with the latest knowledge for neighboring disciplines required for diagnosis and therapy of cough. The clinical chapters also contain a short summary, practical recommendations and a bibliography of their own. Three new simplified algorithms for acute, subacute and chronic cough, round off the diagnostics chapter. Highlights: Dedicated to respiratory specialists treating adult patients referred to for cough We present 3 clinical algorithms for diagnosis of acute, subacute and chronic cough The most frequent causes of cough as a symptom and Cough as a disease on his own are described Establishing specialist cough clinics in Germany advocated